The clinical management of hepatocellular carcinoma in China: Progress and challenges - Shan, Shan; Jia, Jidong (Clinical and molecular hepatology, 2023)
[...]the University of California San Francisco criteria for liver transplant are adopted and offer HCC patients more transplant opportunities than the Milan criteria but yield a similar post-transplant outcome. [...]this article also discussed multimodal and high-intensity anti-tumor strategies for HCC patients in real-life practices in China, such as the addition of immunotherapy-based systemic therapy to local modalities, which may improve the chance of receiving curative therapy and long-term survival for patients with nonearly-stage HCC. [...]due to poor adherence to long-term HCC surveillance [15], most patients with HCC are in intermediate or advanced stage, which carries a very poor survival rate since such patients are not eligible for curative therapy [16]. [...]the timely updating and advocating of evidence-based HCC guidelines will help improve the quality of care in real-world practice to improve clinical outcomes of HCC patients in China.